(Expansion of Extractive Industries and their Effects on Agricultural Lands in Mukdadiya District - Attia Al-Lahibi, Saddam Mazhar (Journal of Tikrit University for Humanities, 2023)
The study area under consideration is renowned for its agricultural land and its fertility. It has gained a reputation for being a significant producer of various citrus crops, earning it the title of the "Mother of Oranges." Additionally, the region has been known for its cultivation of pomegranates, dates, and other agricultural crops. However, the agricultural sector has experienced a decline in productivity following the events of 2014, particularly in the Mukdadiya district. This decline can be attributed to the rapid expansion and proliferation of extractive industries, specifically quarries, which have encroached upon and diminished the available agricultural land in the Mukdadiya district. The need to do several studies in order to mitigate this issue, which poses significant dangers to agricultural operations within the study region, is evident. The study region was subjected to the installation of gravel and sand production facilities, which led to the identification of significant adverse impacts associated with the extractive sectors. Previously, the issue was subject to examination.